Asymmetric Organocatalytic Michael/Michael/Henry Sequence to Construct Cyclohexanes with Six Vicinal Stereogenic Centers - Chen, Yushuang; Liu, Xiaohua; Luo, Weiwei; Lin, Lili; Feng, Xiaoming (Synlett, 2017)
An efficient, asymmetric, catalytic, triple-cascade reaction between α-keto esters and nitroalkenes to construct cyclohexanes with six vicinal stereogenic centers in good yields and with high enantioselectivities has been established. A bifunctional guanidine–amide organocatalyst proved to be useful for the Michael/Michael/Henry sequence through Brønsted base and hydrogen-bonding cooperative catalysis.
Keywords: asymmetric catalysis; cascade reaction; cyclohexanes; organocatalysis; keto esters; nitroalkenes